Effectiveness of Paradoxical Time-Scheduling Therapy on Physical Fatigue Symptoms, Habitual Action, and Helplessness Toward Change in Women with Post-Traumatic Stress Disorder (PTSD) - Saki, Hananeh; Askarian, Mahnaz; Anasseri, Mehryar (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to determine the effectiveness of paradoxical timetable therapy on physical fatigue symptoms, habitual behavior, and helplessness toward change in women diagnosed with post-traumatic stress disorder (PTSD). This research employed a quasi-experimental method using a pretest-posttest design with two groups. The statistical population included all women in Tehran diagnosed with PTSD who sought psychological treatment at the Amin Psychological Counseling Center in 2024. In this study, 24 individuals were selected through purposive non-random sampling and then randomly assigned to two groups: 12 participants in the experimental group and 12 in the control group. The experimental group participated in six 60-minute sessions of paradoxical timetable therapy. Ultimately, after attrition, 11 participants successfully completed the intervention. The control group did not receive any intervention. Notably, in order to equate the sample sizes, the number of dropouts in the experimental group was randomly mirrored in the control group by removing participants. This study utilized the Physical Fatigue Symptoms Questionnaire, the Reflective Thinking Scale, and the Jones Irrational Beliefs Questionnaire as research instruments. The collected data were analyzed using multivariate analysis of covariance (MANCOVA) and univariate analysis of covariance (ANCOVA). The results indicated a statistically significant difference in post-test mean scores between the experimental and control groups. Paradoxical timetable therapy significantly improved physical fatigue symptoms, habitual behavior, and helplessness toward change in women diagnosed with PTSD.